2005
DOI: 10.1097/01.gco.0000175357.25932.89
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion prevention in gynecologic surgery

Abstract: There has been a wide range of adhesion-reducing substances evaluated in animal models. However, in clinical situations, no adhesion-preventing substance, material, or barrier is unequivocally effective. In view of surgical technique, compared to laparotomy, the laparoscopic approach is associated with less adhesion formation. Temporary abdominal oophoropexy may provide a promising technique to prevent ovarian adhesions. Future research should also be directed toward preventing intrauterine adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…A more recent review considered the application of hyaluronic acid, hydrogel, viscoelastic gel, vitamin E and other substances, as well as modifications of surgical technique (peritoneal non-closure, temporary abdominal oophoropexy, or changing the temperature, humidity or consistency of the gas used in laparoscopic surgery). 18 All of these articles concluded that none of the interventions available provided reliable effectiveness in the prevention of adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent review considered the application of hyaluronic acid, hydrogel, viscoelastic gel, vitamin E and other substances, as well as modifications of surgical technique (peritoneal non-closure, temporary abdominal oophoropexy, or changing the temperature, humidity or consistency of the gas used in laparoscopic surgery). 18 All of these articles concluded that none of the interventions available provided reliable effectiveness in the prevention of adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…1 A variety of complications may result, including pain, infertility and bowel obstruction, and re-operation may be required. Adhesion is responsible for a large number of hospitalizations and substantial financial cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clotting cascade as a result of tissue injury, exudate formation rich in protein-containing substances, the development of fibrin deposits from this protein mass, destruction of these fibrin tissues by plasminogen activators in healthy tissues, collagen storing by fibroblasts after four to five days, and formation of permanent fibrous adhesions are well-known processes contributing to the formation of adhesions (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21][22][23][24][25][26] In this study most patients (94.4%) have a history of laparotomy. However there are not significant differences in PAI score based on previous surgical access (open vs laparoscopic, P=0.352).…”
Section: Figure 1 Peritoneal Adhesion Index (Pai)mentioning
confidence: 99%
“…Adhesions occur after 50-100% of surgical interventions. 1,2 They are often responsible for small bowel obstructions, 3,4 secondary female infertility, ectopic gestation 5,6 and chronic abdominal pains. [7][8][9] The impact of adhesions on surgeon workload and on the healthcare cost is significant.…”
Section: Introductionmentioning
confidence: 99%